Некрасовский «Пророк» и «священный» язык русской революции - Korčinskij, Anatolij (Wiener Slawistischer Almanach, 2024)
The author considers Nikolai Nekrasov’s poem “The Prophet” as a key to understanding the complex interaction of different tendencies in the discourse and political imaginary of Russian radicals (‘nihilists’-sixties, narodniks, neo-narodniks) associated with the processes of secularization and desecularization, which become more evident in the modern optics of ‘postsecularization’. The thesis of different registers of understanding religion and secular order, the ‘sacred’ and the ‘secular’ in the political language of 1860s–1870s, which include both their strict differentiation and the possibility of translation from Christian language to the language of revolutionary politics, and the new sacralization of the radicals’ political discourse, is substantiated in the article. Nekrasov, according to the author, captures the complexity and hybrid nature of the political language of the revolutionary generation of the 1870s.